Багатофункціональна радіоелектронна система для тренувань біатлоністів - Пенчук, А. Е. (ХНУРЕ, 2019)
The developed laser infantry simulator, in contrast to foreign analogues, provides the protection of athletes and spectators from laser radiation, since the laser emitter is activated only if the rifle is directed to the target, and its price, taking into account the production in Ukraine, will be lower